Total Quality Management, Customer Relationship Management, Patient Satisfaction as Determinants of Behavioral Intention to Use Private Hospital Services - Hadinata, Valencia; Berlianto, Margaretha Pink; Antonio, Ferdi (FORIKES, 2025)
Optimal service quality is expected to meet patient expectations, which is essentially an effort to exceed their expectations of the services they receive. This study analyzed the influence of total quality management dimensions and customer relationship management dimensions on patient satisfaction and behavioral intentions in private hospitals in Indonesia. This study applied a management approach. This study adopted a judgmental sampling method. The criteria for the sample population were patients who have received treatment at the Siloam Hospital outpatient clinic in Jakarta. The sample size in this study was 241 respondents. As results, total quality management had a positive effect on patient satisfaction. Customer relationship management had a positive effect on patient satisfaction. Customer relationship management had a positive effect on behavioral intention. Patient satisfaction was proven to mediate the relationship between customer relationship management and behavioral intention. Patient satisfaction had a positive effect on behavioral intention. As conclusion, the results of this study also show that there is a contribution of something new in this research model, namely the influence of three dimensions of customer relationship management variables that directly affect patient satisfaction and behavioral intention at Siloam Hospital Jakarta. The dimensions of this variable include customer service, communication, and information technology usage.Keywords: total quality management; customer relationship management; behavior intention; patient satisfaction